PENGARUH PEMBERIAN BAYFOLAN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAYAM (AMARANTHUS TRICOLOR. L) VARIETAS AMARIN DI DESA SANUR DENPASAR - Supadma, I Made; Sukerta, I Made; Raka, I Dewa Nyoman (Agrimeta: Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2018)
Research on the effect of bayfolan on the growth and yield of spinach plants (Amaranthus tricolor L) of amarin varieties in Sanur Denpasar village was done in greenhouse, from January 5 to February 15, 2018. The objective of this research was to know the effect of the treatment of bayfolan leaf fertilizer on growth and the result of spinach plants. This study used Randomized Block Design (RAK) with 6 treatments and repeated 4 times, so that 24 treatment was obtained. The data obtained will be analyzed using statistical analysis, if treatment of real effect will be continued with BNT test. Parameters observed were plant height, number of leaves, leaf area, stem circumference, number of branches, fresh weight and dry weight. The experimental results showed unreal results on all observation parameters. Experimental results show the best growth trend and best result on the treatment of bayfolan with concentration 0.15 ml / 1 liter per plant.